Three-dimensional thermal management: Biomass aerogel with super-hydrophilicity for high-efficiency solar evaporation via environmental energy synergy - Li Jiang; Yanyou Huang; Liangdong Ye; Yuling Lv; Ruibin Shen; Wei Wang; Yanlan Pan; Zuocai Zhang; Shaorong Lu (Desalination, 2026)

The initiation and resuspension characteristics of (micro)plastics from varied depositional environments under hydraulic disturbance - Yuling Chen; Li Lin; Xiong Pan; Yuqi Zhang (Journal of Soils and Sediments, 2026)

Preliminary insight into the ability of bovine-derived Loigolactobacillus coryniformis XJ-C-L1-produced acid-dependent extracellular metabolites to inhibit MRSA growth and biofilm formation in milk - Yuling Guo; Wenjing Wang; Yaqian Liang; Meihui Tian; Ming Wu; Junkai Wang; Haihong Hao; Yu Pan (International Dairy Journal, 2026)

Bifunctional starch nanoparticles for achieving recyclable interfacial biocatalysis within a narrow pH range - Liang Qi; Yujing Zhou; Yuling Pan; Cong Zhang; Xiaojuan Xu; Xin Cai (Carbohydrate Polymers, 2026)

Sustainable chitosan composite foams: Synergistic hydroxyapatite nanowires / phytic acid-melamine hybridization for reliable fire warning and efficient flame suppression - Zhirong Xu; Pengyu Xing; Yong Pan; Yuling Xiao (Carbohydrate Polymers, 2026)

Ameliorative Effects of an Antioxidant and Anti-Inflammatory Limosilactobacillus fermentum TG017 on DSS-Induced Ulcerative Colitis in Mice - Qianhao Hou; Yuling Li; Zuanyuan Huang; Honghua Hu; Xin Li; Jinyuan Zhang; Wenying Duan; Songsong Pan; Zetian Wang; Xiaodong Liu; Wei Xu; Lijun Liao (Probiotics and Antimicrobial Proteins, 2026)

Understanding the tradeoff between the flood risk and the hydropower benefit from the integrated flood control operation of a reservoir group and a flood detention basin - Zhenyu Mu; Dedi Liu; Zhenyu Wang; Yuling Zhang; Pan Liu; Lihua Xiong; Jie Chen; Hua Chen; Jiabo Yin (Journal of Hydrology, 2026)

l-Lysine effects on myosin carbonylation in metal-catalyzed oxidation: Implications for thermal gelation - Yuling Liu; Yuqi Wu; Ge Han; Jiaxin He; Yawen Wang; Jinfeng Pan; Shengjie Li (Food Research International, 2026)

Breaking acidification-ammonia inhibition cycle in anaerobic co-digestion with alkaline lime mud via synthetic microbial consortium - Linpei Liu; Yao Ren; Xiaoru Chen; Jun Wang; Yuling Huang; Pan Zhang; Qili Zhu; Han Qin; Furong Tan; Mingxiong He; Yong Zhuang (Journal of Environmental Chemical Engineering, 2026)

Assessing the variations of the available flood storage capacity in a flood retention basin due to the changing environment - Yuling Zhang; Dedi Liu; Zhenyu Wang; Zhenyu Mu; Jiaoyang Wang; Pan Liu; Lihua Xiong; Jie Chen; Hua Chen (Journal of Environmental Management, 2026)

Dynamic Changes in Serum Biochemical Indices and Alternative Splicing Events Revealed Molecular Regulatory Mechanisms in Rainbow Trout Under Copper Stress - Junhao Lu; Jinqiang Quan; Jing Zhou; Yucai Pan; Jiahui Zhang; Ziguo Wang; Yuling Qu (Marine Biotechnology, 2026)

Recent heat wave across the Yunnan-Guizhou plateau and its impact on alpine lakes - Jiabin Peng; Junxu Chen; Xiaohui Pan; Yuling Luo; Siqi Feng; Tie Liu; Xi Chen (Journal of Cleaner Production, 2026)

Biochar and moisture variability shape soil carbon pools via microbial carbon-degrading genes - Yue Pan; Tingting Tan; Jie Meng; Hongpeng Guo; Yingbo Dong; Yukui Cui; Na Yu; Xinxin Jin; Yuling Zhang; Hongtao Zou; Nanthi Bolan; Kadambot H.M. Siddique (Journal of Environmental Management, 2026)

Simulation of the impact of the carbon peak target allocation method on the energy structure of electricity generation—based on electricity market equilibrium modeling - Qing Xu; Jue Cui; Feng Dong; Yuling Pan (Clean Technologies and Environmental Policy, 2026)

Effect of organic amendments on soil organic carbon fractions, water retention, and mechanical properties in a Chinese Alfisol - Yue Pan; Danyang Wang; Tingting Tan; Jing An; Xinxin Jin; Hongtao Zou; Yuling Zhang; Na Yu; Kadambot H.M. Siddique (Soil and Tillage Research, 2025)

Genome-wide identification and analysis of paclobutrazol-resistance gene family in cotton and the positive role of GhPRE3 in salt stress and drought stress resistance - Shuaikang Geng; Jingjing Zhai; Bingkai Cui; Huiyun Shan; Zili Liu; Jiahui Li; Cong Wang; Yuling Liu; Pengtao Li; Quanwei Lu; Zihan Xiao; Xiaoping Pan; et al. (Functional & Integrative Genomics, 2025)
Compared with other transcription factors, much less studies have been performed on paclobutrazol-resistance (PRE), a subgroup of the extensive bHLH transcription factor gene family, and the research in cotton was also limited. By utilizing the PRE genes and their conserved domains identified in Arabidopsis, a total of 23, 22, 11, and 12 PRE genes were identified from two major cultivated cotton species and their two ancestors, respectively. The cotton PRE gene family was categorized into three subgroups based on evolutionary tree analysis. Motif and intron analyses indicated that the PRE gene has remained highly conserved throughout evolution. Collinearity analysis indicated that gene duplication, particularly through fragment replication, has significantly contributed to the expansion of the cotton PRE family. An exploration of the conserved elements within the PRE gene family uncovered numerous elements associated with plant stress resistance. Additionally, cotton transcriptome and qRT-PCR analysis showed that PRE genes were associated with a variety of abiotic stresses, including salt, drought, and cold treatments. Subcellular localization experiments indicated that the GhPRE3 gene is associated with membrane proteins. Finally, we selected the GhPRE3 gene for a VIGS experiment, which revealed that under salt stress and drought stress conditions, the wilting of leaves in the GhPRE3- silenced plants was significantly more severe than that observed in the control group, with T-AOC levels notably lower and MDA levels significantly higher. Overexpression of GhPRE3 enhanced seed germination and root development in transgenic Arabidopsis thaliana under salt stress and drought stresses. This suggests that GhPRE3 plays a positive regulatory role in cotton tolerance to salt and drought stressed, providing a reference for molecular genetic breeding of cotton with salt and drought tolerance.

Assessment of stability differences among various grassland biomes under severe drought in the northern China and Tibetan Plateau - Haile Zhao; Yi Zhou; Xin Chen; Yuan Qi; Yuyang Chang; Yuchao Luo; Xingjie Yin; Yuling Jin; Zhihua Pan; Pingli An (Agriculture, Ecosystems & Environment, 2025)

A novel nonaerated passive constructed wetland for high-efficiency nitrogen and phosphorus removal based on slow-release oxygen regulation - Bing Liao; Xinyu Quan; Yuling Yang; Xinrui Huang; Ziyi Wang; Zhicheng Pan (Journal of Environmental Chemical Engineering, 2025)

Dam operation changed the transport patterns of microplastics - from a global perspective - Yuling Chen; Li Lin; Yi Li; Yu Gao; Lei Dong; Xiong Pan; Ziwei Guo (Environmental Pollution, 2025)

A pilot-scale study of biological activated carbon (BAC) filter for secondary effluent of petrochemical wastewater: Performance and mechanisms - Weiqing Xu; Yuling Liu; Jinkai Xue; Jie Pan; Yaozhong Zhang; Xiaopeng Qiu; Xing Zheng (Journal of Environmental Chemical Engineering, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

China's non-energy-intensive sectors have greater carbon reduction potential: Based on a three-tier SDA approach from energy substitution perspective - Chang Qin; Feng Dong; Yangfan Li; Xiaoyun Zhang; Yuling Pan; Caixia Li; Jue Cui (Environmental Impact Assessment Review, 2025)

Low-cost Ca/Mg co-modified biochar for effective phosphorus recovery: Adsorption mechanisms, resourceful utilization, and life cycle assessment - Ming Chen; Yifan Liu; Junchao Pan; Yuling Jiang; Xueyan Zou; Yangyang Wang (Chemical Engineering Journal, 2024)

Correction: Identification and biochemical characterization of a novel halolysin from Halorubellus sp. PRR65 with a relatively high temperature activity - Yuling Hao; Yu Jin; Aodi Zhang; Xinran Jiang; Ming Gong; Cunlong Lu; Ruru Pan; Shaoxing Chen (World Journal of Microbiology and Biotechnology, 2024)

Identification and biochemical characterization of a novel halolysin from Halorubellus sp. PRR65 with a relatively high temperature activity - Yuling Hao; Yu Jin; Aodi Zhang; Xinran Jiang; Ming Gong; Cunlong Lu; Ruru Pan; Shaoxing Chen (World Journal of Microbiology and Biotechnology, 2024)

Mapping the dynamics of intensive forage acreage during 2008–2022 in Google Earth Engine using time series Landsat images and a phenology-based algorithm - Haile Zhao; Yi Zhou; Guoliang Zhang; Xin Chen; Yuyang Chang; Yuchao Luo; Yuling Jin; Zhihua Pan; Pingli An (Computers and Electronics in Agriculture, 2024)

Evaluation of Opaque-2 effects on popping characteristics using iTRAQ-based proteome profiles in popcorn - Yongbin Dong; Qi Zheng; Junjie Zhu; Qingling Shi; Siqi Jiang; Mengying Pan; Xinyue Zhang; Long Zhang; Yuling Li (Euphytica, 2024)

The impacts of aridification on land surface phenological changes in the farming-pastoral ecotone of northern China based on the climatic zoning method - Guoliang Zhang; Yuling Jin; Yi Zhou; Xin Chen; Haile Zhao; Sicheng Mao; Yuchao Luo; Siyu Chen; Xiuyue Wu; Zhihua Pan; Pingli An; Peiyi Zhao (Theoretical and Applied Climatology, 2024)

Lysosome-targeted ruthenium(II) complex encapsulated with pluronic® F-127 induces oncosis in A549 cells - Nanlian Pan; Yuqing Zhang; Minying Huang; Zhijun Liang; Yao Gong; Xide Chen; Yuling Li; Ciling Wu; Zunnan Huang; Jing Sun (JBIC Journal of Biological Inorganic Chemistry, 2024)

Distinctive interphasial properties and high structural reversibility endowed by B-/CN– electrolyte additive and its superior electrochemical performance for graphite/LiCoO2 pouch cells - Shuai Chen; Xinyang Wen; Yili Chen; Zhiyong Xia; Qiurong Chen; Lingling Huang; Haonan Huang; Haowen Pan; Yuling Fu; Jiarong He; Weishan Li (Chemical Engineering Journal, 2024)

Expression, purification, and enzymatic characterization of an extracellular protease from Halococcus salifodinae - Tao Hong; Ruru Pan; Juntao Ke; Yuqing Luo; Yuling Hao; Liangzhong Chen; Demei Tu; Yongpei Dai; Tingting Chen; Shaoxing Chen (Brazilian Journal of Microbiology, 2023)

Land use/cover changes and subsequent water budget imbalance exacerbate soil aridification in the farming-pastoral ecotone of northern China - Guoliang Zhang; Xin Chen; Yi Zhou; Haile Zhao; Yuling Jin; Yuchao Luo; Siyu Chen; Xiuyue Wu; Zhihua Pan; Pingli An (Journal of Hydrology, 2023)

Novel facile synthesis and room-temperature sintering of copper nanowires for solution-processed transparent conductive films - Qing Liu; Yibo Wu; Yong Li; Yuling Shi; Qianqian Pan; Danlong Yang; Tao Wang (Chemical Engineering Journal, 2023)

Correction to: Improving the specific activity and stability of alkaline pectinase PEL3 through SpyTag/SpyCatcher cyclization - Chao Du; Siqin Tan; Lin Liu; Yuling Zhou; Pan Wu; Guimin Zhang (Biotechnology Letters, 2023)

Examining the importance of built and natural environment factors in predicting self-rated health in older adults: An extreme gradient boosting (XGBoost) approach - Yiyi Chen; Xian Zhang; George Grekousis; Yuling Huang; Fanglin Hua; Zehan Pan; Ye Liu (Journal of Cleaner Production, 2023)

Comparative Analysis of the Therapeutic Effects of Fresh and Cryopreserved Human Umbilical Cord Derived Mesenchymal Stem Cells in the Treatment of Psoriasis - Zhifeng Wang; Yifan Hu; Xiaoyu Wang; Youdong Chen; Danfeng Wu; Houli Ji; Cuicui Yu; Jingmeng Fang; Chunrong Pan; Lianjian Wang; Shouxin Wang; Yinhong Guo; et al. (Stem Cell Reviews and Reports, 2023)

Hly176B, a low-salt tolerant halolysin from the haloarchaeon Haloarchaeobius sp. FL176 - Shenao Zhang; Feilong Chen; Juntao Ke; Yuling Hao; Ruru Pan; Tao Hong; Yongpei Dai; Shaoxing Chen (World Journal of Microbiology and Biotechnology, 2023)

Improving the specific activity and stability of alkaline pectinase PEL3 through SpyTag/SpyCatcher cyclization - Chao Du; Siqin Tan; Lin Liu; Yuling Zhou; Pan Wu; Guimin Zhang (Biotechnology Letters, 2023)

Premature mortality attributable to NO2 exposure in cities and the role of built environment: A global analysis - Jian Song; Yuling Wang; Qin Zhang; Wei Qin; Rubing Pan; Weizhuo Yi; Zhiwei Xu; Jian Cheng; Hong Su (Science of The Total Environment, 2023)

The effect of economic growth pressure on green technology innovation: Do environmental regulation, government support, and financial development matter? - Hongyang Yu; Jinchao Wang; Jian Hou; Bolin Yu; Yuling Pan (Journal of Environmental Management, 2023)

The increased medical burden associated with frailty is partly attributable to household solid fuel: A nationwide prospective study of middle-aged and older people in China - Xiaoyu Jin; Yuling Wang; Yudong Wu; Yunfeng Liang; Yuxuan Li; Xiaoni Sun; Shuangshuang Yan; Lu Mei; Junwen Tao; Jian Song; Rubing Pan; Weizhuo Yi; et al. (Science of The Total Environment, 2023)

Is China approaching the inflection point of the ecological Kuznets curve? Analysis based on ecosystem service value at the county level - Yuling Pan; Feng Dong; Congcong Du (Journal of Environmental Management, 2023)

How rainfalls influence urban traffic congestion and its associated economic losses at present and in future: taking cities in the Beijing-Tianjin-Hebei region, China for example? - Yi Zhou; Sicheng Mao; Haile Zhao; Guoliang Zhang; Xin Chen; Yuling Jin; Lin Xu; Zhihua Pan; Pingli An; Fei Lun (Theoretical and Applied Climatology, 2022)

Grazing and global change factors differentially affect biodiversity‐ecosystem functioning relationships in grassland ecosystems - Miao He; Yuhan Pan; Guiyao Zhou; Kathryn E. Barry; Yuling Fu; Xuhui Zhou (Global Change Biology, 2022)
Grazing and global change (e.g., warming, nitrogen deposition, and altered precipitation) both contribute to biodiversity loss and alter ecosystem structure and functioning. However, how grazing and global change interactively influence plant diversity and ecosystem productivity, and their relationship remains unclear at the global scale. Here, we synthesized 73 field studies to quantify the individual and/or interactive effects of grazing and global change factors on biodiversity‐productivity relationship in grasslands. Our results showed that grazing significantly reduced plant richness by 3.7% and aboveground net primary productivity (ANPP) by 29.1%, but increased belowground net primary productivity (BNPP) by 9.3%. Global change factors, however, decreased richness by 8.0% but increased ANPP and BNPP by 13.4% and 14.9%, respectively. Interestingly, the strength of the change in biodiversity in response to grazing was positively correlated with the strength of the change in BNPP. Yet, global change flipped these relationships from positive to negative even when combined with grazing. These results indicate that the impacts of global change factors are more dominant than grazing on the belowground biodiversity‐productivity relationship, which is contrary to the pattern of aboveground one. Therefore, incorporating global change factors with herbivore grazing into Earth system models is necessary to accurately predict climate‐grassland carbon cycle feedbacks in the Anthropocene.

Effects of roasting and deodorisation on 3-monochloropropane-1, 2-diol esters, 3, 4-benzopyrene and trans fatty acids in peanut oil - Pan Gao; Yuling Zheng; Hui Liu; Wei Yang; Chuanrong Hu; Dongping He (Food Additives & Contaminants: Part A, 2022)

How to optimize provincial PM2.5 reduction targets and paths for emerging industrialized countries? Fresh evidence from China - Yuling Pan; Feng Dong (Environmental Science and Pollution Research, 2021)

Economic policy choice of governing haze pollution: evidence from global 74 countries - Feng Dong; Xiaojie Zhang; Yajie Liu; Yuling Pan; Xiaoyun Zhang; Ruyin Long; Ziyuan Sun (Environmental Science and Pollution Research, 2021)

What contributes to the regional inequality of haze pollution in China? Evidence from quantile regression and Shapley value decomposition - Feng Dong; Bolin Yu; Yuling Pan; Yifei Hua (Environmental Science and Pollution Research, 2020)

Exogenous salicylic acid regulates reactive oxygen species metabolism and ascorbate–glutathione cycle in Nitraria tangutorum Bobr. under salinity stress - Yongqing Yan; Chenhui Pan; Yuling Du; Danyang Li; Wei Liu (Physiology and Molecular Biology of Plants, 2018)

Molecular cloning and characterization of squalene synthase from Matricaria recutita L. - Xiaojuan Hou; Yuling Tai; Shuping Ling; Dahui Li; Chunxiao Guo; Jiameng Sun; Guifang Pan; Yi Yuan (Acta Physiologiae Plantarum, 2018)

CO 2 storage in coal to enhance coalbed methane recovery: a review of field experiments in China - Zhejun Pan; Jianping Ye; Fubao Zhou; Yuling Tan; Luke D. Connell; Jingjing Fan (International Geology Review, 2018)

Determination and optimization of a strong promoter element from Bacillus amyloliquefaciens by using a promoter probe vector - Yuling Liao; Bin Wang; Yanrui Ye; Li Pan (Biotechnology Letters, 2018)

Optimization of the purine operon and energy generation in Bacillus amyloliquefaciens for guanosine production - Yuling Liao; Yanrui Ye; Bin Wang; Li Pan (Biotechnology Letters, 2017)

Nanoscale zerovalent iron-mediated degradation of DDT in soil - Yuling Han; Nan Shi; Huifang Wang; Xiong Pan; Hua Fang; Yunlong Yu (Environmental Science and Pollution Research, 2016)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)